Acute and Subchronic Toxicity Assessment of Aerial Parts of Ferula persica in Female Mice - M Soleimani Far; F Mojab; S Arbabi Bidgoli (Institue of Medicinal Plants, ACECR, 2019)
Background: Ferula species have shown wide range of pharmacological properties but there is no study on oral safety profile of Ferula persica due to standard toxicology guidelines. Objective: This study aimed to evaluate the acute and subchronic oral toxicity of the alcoholic extract of the aerial parts of Ferula persica to provide its safe dose for long term oral administrations as a possible herbal remedy. Methods: Hydroalcoholic extract from leaves and flowers was provided and standardized then acute and repeated dose oral toxicity tests were performed by OECD 423 and 407 guidelines. In the subchronic test, animals in each treatment group received hydroalcoholic extracts 1000 mg/kg/day. At the end of study mortality, weight changes, biochemical, hematological and histopathological studies were performed. Results: Acute toxicity test did not show any mortality and any sign of toxicity up to 2000 mg/kg in a 14 days study and in the repeated dose toxicity test, no sign of organ toxicity was detected in doses up to 1000 mg/kg during 28 days continuous study according to clinical, hematological, biochemical and histopathological evidences in liver, kidney, uterus, ovaries, heart, lung and spleen of animals. Conclusion: This study has revealed the safety of Ferula persica herbal extract in acute and subchronic oral administrations in doses up to 2000 and 1000 mg/kg respectively. We have defined the limit of oral long term exposure (No Observed Adverse Effects Level /NOAEL) in doses up to 1000 mg/kg which could suggest these aerial parts of Ferula persica as a new herbal remedy for future medical and nutritional purposes.